Numerical simulation of the crushing process of a corrugated composite plate - Sokolinsky, Vladimir S.; Indermuehle, Kyle C.; Hurtado, Juan A. (Composites. Part A, Applied science and manufacturing, 2011)
The significant potential of composite materials as highly effective energy absorbers has contributed to their increasing usage in the aerospace, automotive, and railway industries. Traditionally, the development of crashworthiness composites design relies upon laborious and costly experimental testing. Therefore, the ability to simulate accurately the crushing response of composites and their energy absorption mechanisms can significantly reduce the product development cycle and cost. The present work presents a physics-based finite element model of a corrugated carbon–epoxy fabric composite plate subject to quasi-static crushing. The model accounts for both intralaminar (in-plane) and interlaminar (delamination) failure mechanisms. The in-plane response of the fabric plies is modeled using a proposed constitutive model that has been implemented in the commercial finite element code Abaqus/Explicit; and the delamination response of the composite plate is simulated using the cohesive surface capability in Abaqus. The results of the Abaqus/Explicit simulations show very good quantitative and qualitative agreement with the experimental data, thus demonstrating that the proposed methodology and tools can be used for realistic crush simulations of composite structures.